From the Persistence of Ableism to its Deconstruction in the Evolution of Collective and Individual Narratives around Prosthetic Amputee Bodies - Valentine Gourinat; Paul-Fabien Groud (Amnis)
This article traces the evolution of the image of the amputated body fitted with prosthetic devices in collective and individual narratives from the early 20th century to the present day in European and North American societies. As these narratives are persistently permeated by an ableist lens and ideology, they are not devoid of socio-political issues and consequences for the people concerned. Based on these narratives, this paper proposes a socio-anthropological analysis of their historical development and their impact on representations of disability, insofar as they are a tool for transmitting social and collective values. More specifically, the aim is to question the fascination with prosthetics and the culture of the high-performance amputee body, which are vectors of ableist injunctions and ideals. The aim is also to highlight the complexity and variety of individual approaches in the face of persistent and collective normalisation over time.